Serious Game Development Model Based on the Game-Based Learning Foundation - Rickman Roedavan; Bambang Pudjoatmodjo; Yahdi Siradj; Sazilah Salam; BQ Desy Hardianti (Journal of ICT Research and Applications, 2021)
Serious games or applied games are digital games applied in serious fields such as education, advertising, health, business, and the military. Currently, serious game development is mostly based on the Game Development Life Cycle (GDLC) approach. A serious game is a game product with unique characteristics that require a particular approach to its development. This paper proposes a serious game development model adapted from the Game-Based Learning Foundation. This paper’s main contribution is to enhance knowledge in the game development field and game-related application research. The proposed model was validated using the relativism approach and it was used to develop several game prototypes for universities, national companies, and the military.